Red Rice in Himachal Pradesh: History, Tradition and Uses - Thakur, Ashok K.; Himangini; Kumari, Neelam (International Journal of Economic Plants, 2020)
Red rice or Laal Dhaan (Oryza sativa L.) is a famous land race of mid and high hills of South Western Himalayas in Himachal Pradesh, Jammu & Kashmir and some parts of Uttrakhand. Being a traditional crop of Himachal Pradesh, red rice is deeply knitted with traditional rituals and used in various folk dishes and snacks. The key special uses include; Phooli Moorhi, Sookhi Moorhi, Chewrhior Hari Moorhi, Shakli or Sanse and the flour of red rice is also used to make Sidhku. Red rice is also used for making beverages in many areas of the state. Lugrhi, a brewed drink prepared from red rice, is famous in Kullu district. The husk separated while making Chewrhi is used as medicine to cure poisoning symptoms in cattle. The decoction made from red rice and lassi is used to cure dysentery in human beings. The rice water separated after cooking rice is fed to pregnant and lactating women as nutritional food supplement. The demand of nutraceutically rich food is increasing day by day. Keeping in view, the increased demand and shrinking area under the red rice, a concrete policy and marketing strategy is urgently required to motivate farmers and boost the cultivation of rice in its traditional areas of cultivation. A well-developed postharvest value chain is urgently required so that this nutraceutically rich gift of nature reaches the consumer across the globe.